A Hoard of Bronze Objects from Wester Ord, Ross-shire, and an Early Iron Age Burial at Blackness Castle, Linlithgowshire - Richardson, James S (Proceedings of the Society of Antiquaries of Scotland, 1925)
A collection of bronze objects, one of which the author recognised as having been illustrated in Dr Joseph Anderson's "Scotland in Pagan Times, Bronze and Stone Ages" was recovered from an antiques shop. The hoard consists of two socketed axes, a curved socketed tool, a gouge, a socketed knife, a penannular armlet, and two fragments of a neck-ring. All these objects belong to the end of the Bronze Age, exhibit the same degree of patination, and have now been identified as the hoard unearthed from under the corner of a large earth-fast boulder on the farm of Wester Ord, on the Invergordon property, in 1859, where apparently they had been buried wrapped up in cloth. An extended prone burial with a bronze armlet was found in the grounds of Blackness Castle. The north-south aligned grave was lined with small water worn stones and the skeleton was identified as a female aged approximately 30 years.